PENERAPAN POLA ASUH DEMOKRATIS DALAM MENUMBUHKAN MINAT BACA GENERASI ALPHA - Imroatun Shaleha; Nur Riani (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2023)
The tradition of reading in the family is one of the habituations of parents in fostering interest in reading. The alpha generation is a child born in the digital era which is certainly very close to technology. People's parenting plays a role in growing children's reading standards. So, this study aims to determine the application of democratic parenting in Kecicang Asri Housing, Karangasem, Bali in fostering interest in reading. In addition, it is also to find out the causal factors and efforts of parents in growing interest in reading. The qualitative research with this descriptive approach uses the method of collecting observational data, interviews, and documentation. The results are, (1) the democratic parenting style provided by parents in fostering interest in reading is to provide a variety of reading books, educational games, and put up pictorial posters in the child's room. (2) Factors causing children's difficulty in cultivating interest in reading due to lack of care, habituation, and assistance from parents (internal) as well as from environmental factors (external). (3) The efforts made by parents in fostering interest in reading are by habituating to the bookstore, providing educational children's games, putting up posters and reading in the children's room.  Abstrak Tradisi membaca dalam keluarga menjadi salah satu pembiasaan orang tua dalam menumbuhkan minat baca. Generasi alpha merupakan anak yang lahir di era digital yang tentunya sangat dekat dengan teknologi. Pola asuh orang berperan dalam menumbuhkan minabat baca anak. Sehingga penelitian ini bertujuan untuk mengetahui penerapan pola asuh demokratis di Perumahan Kecicang Asri, Karangasem, Bali dalam menumbuhkan minat baca. Selain itu juga untuk mengetahui faktor penyebab serta upaya orang tua dalam penumbuhan minat baca. Adapun penelitian kualitatif dengan pendekatan deksriptif ini menggunakan metode pengumpulan data observasi, wawancara, dan dokumentasi. Hasil dari penelitian ini adalah, (1) pola asuh demokratis yang diberikan orang tua dalam menumbuhkan minat baca adalah menyediakan berbagai buku bacaan, permainan yang mendidik, dan memasang poster bergambar di kamar anak. (2) Faktor penyebab kesulitan anak dalam meumbuhkan minat baca karena kurang mendapatkan pengasuhan, pembiasaan, dan pendampingan dari orang tua (internal) serta dari faktor lingkungan tempat tinggal (eksternal). (3) Upaya yang dilakukan orang tua dalam menumbuhkan minat baca adalah dengan pembiasaan ke toko buku, memberikan permainan anak yang mendidik, memasang poster bergambar dan terdapat bacaan di kamar anak.